2019
DOI: 10.1080/13506285.2019.1593272
|View full text |Cite
|
Sign up to set email alerts
|

Attentional suppression is delayed for threatening distractors

Abstract: According to the threat-capture hypothesis, fear-related stimuli have a high attentional priority. As a result, irrelevant-but-salient stimuli interfere more with a visual search task when they are perceived as threatening. We investigated the neural basis for behavioral interference in conditions that promote attentional suppression of distracting stimuli (i.e., easy search with fixed target/distractor roles). In Experiment 1, participants discriminated the shape of a neutral target (a flower), which competed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
(96 reference statements)
1
8
1
Order By: Relevance
“…Finally, the lack of attentional bias to angry faces in the pixel task is also inconsistent with evidence of an early attentional bias to threatening faces or objects when the threatening stimulus was task-irrelevant (Burra et al, 2016(Burra et al, , 2017(Burra et al, , 2019. However, faces in the pixel task of the current experiment were irrelevant and entirely outside the focus of attention, whereas in previous studies, the targets were faces competing for selection with irrelevant facial expressions that were within the attentional focus.…”
Section: Discussioncontrasting
confidence: 88%
“…Finally, the lack of attentional bias to angry faces in the pixel task is also inconsistent with evidence of an early attentional bias to threatening faces or objects when the threatening stimulus was task-irrelevant (Burra et al, 2016(Burra et al, , 2017(Burra et al, , 2019. However, faces in the pixel task of the current experiment were irrelevant and entirely outside the focus of attention, whereas in previous studies, the targets were faces competing for selection with irrelevant facial expressions that were within the attentional focus.…”
Section: Discussioncontrasting
confidence: 88%
“…Finally, the lack of attentional bias to angry faces in the pixel task is also inconsistent with evidence of an early attentional bias to threatening faces or objects when the threatening stimulus was task-irrelevant (Burra et al, 2016, 2017, 2019). However, faces in the pixel task of the current experiment were irrelevant and entirely outside the focus of attention, whereas in previous studies, the targets were faces competing for selection with irrelevant facial expressions that were within the attentional focus.…”
Section: Discussionmentioning
confidence: 81%
“…This seems to be in accordance with the pattern that the attentional biases toward threat framework suggests; specifically, that an attentional capture by the threat is followed by a delayed disengagement, ultimately resulting in a hypervigilance-avoidance behavior. Although the hypervigilance-avoidance hypothesis had been initially proposed for phobic populations (Mogg et al, 2004), it has also been shown in nonfearful participants (Berdica et al, 2018; Burra et al, 2019; Trujillo et al, 2021). A recent study (Liesefeld et al, 2017) using salient task-irrelevant distractors (although not emotionally charged ones) proposed a chain of attentional enhancement and suppression mechanisms based on EEG data.…”
Section: Methodsmentioning
confidence: 99%